Patient outcomes following second surgery for recurrent glioblastoma. (April 2016) - Brandes, Alba A; Bartolotti, Marco; Tosoni, Alicia; Poggi, Rosalba; Bartolini, Stefania; Paccapelo, Alexandro; Bacci, Antonella; Ghimenton, Claudio; Pession, Annalisa; Bortolotti, Carlo; Zucchelli, Mino; Galzio, Renato; et al.
Background: The most appropriate management of recurrent glioblastoma is still controversial. In particular, the role of surgery at recurrence remains uncertain.Patients & methods: From our Institutional data warehouse we analyzed 270 consecutive patients who received second surgery for recurrent glioblastoma, to assess survival after second surgery, and to evaluate prognostic factors.Results: Complete resection was found in 128 (47.4%) and partial resection in 142 patients (52.6%). Median survival from second surgery was 11.4 months (95% CI: 10.0–12.7). Multivariate analysis showed that age (p = 0.001), MGMT methylation (p = 0.021) and extent of surgery (p < 0.001) are associated with better survival.Conclusion: A complete resection should be the goal for second resection and younger age and MGMT methylation status might be considered in the selection of patients.